Some Chaetophorales from Hartala Lake, Maharashtra - and A. K. Jawale2, J. S. Dhande1 (Recent Research in Science and Technology, 2011)
Present communication deals with ten taxa of different genera of Chaetophorales as Stigeoclonium Kuetz., Chaetophora Ã‚Â Schrank, Aphanochaete A. Braun, Protococcus Agardh, Chaetopeltis Berthold, Coleochaete Brebisson, and Chaetosphaeridium Klebahn. Out of which Stigeoclonium farcatum Berth. S. variabile (Naegeli) Islam, Chaetophora attenuata Hazen, Chaetopeltis orbicularis Berthold f.minor Ã‚Â Moebius are for the first time reported from Maharashtra while Stigeoclonium subsecundum (Kuetz.) Kuetz. var. tenue Nordst. emend. for the first time recorded from India.